2020
DOI: 10.1088/1757-899x/780/6/062049
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation dynamics based on NDVI in Yangtze River Basin (China) during 1982-2015

Abstract: Knowledge of vegetation dynamics is important for the sustainability of natural resources and understanding the changes in ecosystems and its impact to earth’s environment. We have carried out analysis of GIMMS (Global inventory modelling and mapping studies) NDVI3g (third generation normalized difference vegetation data for the period 1982-2015. Based on the Linear Regression (LR) analysis, the Mann-Kendall (MK) test with Sen’s slope estimator and Kriging interpolation method, we have investigated the spatiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Figure 8 show the results of spatial and temporal alterations of NDVI in the Jialing River basin, from which it can be seen that: the alterations of vegetation cover in the basin are mainly concentrated in the northern area of Jialing River, while the southern site does not show large fluctuations due to the gentle topography and urban concentration. According to the trend of NDVI values from 1998 to 2020, it can be seen that the NDVI values in the Jialing River basin show an increasing trend, indicating a gradual increase in vegetation cover from the 1990s, which is consistent with the results of NDVI increase in the Yangtze River basin simulated by Cui et al 33 . Zhou et al showed that due to the large-scale soil and water conservation measures implemented in southwest China, the increase in vegetation cover in the Jialing River basin has significantly increased, while the effect of increased vegetation cover on rivers in the basin is mainly focused on sediment changes, while the effect of runoff changes is not obvious 22 .…”
Section: Discussionsupporting
confidence: 88%
“…Figure 8 show the results of spatial and temporal alterations of NDVI in the Jialing River basin, from which it can be seen that: the alterations of vegetation cover in the basin are mainly concentrated in the northern area of Jialing River, while the southern site does not show large fluctuations due to the gentle topography and urban concentration. According to the trend of NDVI values from 1998 to 2020, it can be seen that the NDVI values in the Jialing River basin show an increasing trend, indicating a gradual increase in vegetation cover from the 1990s, which is consistent with the results of NDVI increase in the Yangtze River basin simulated by Cui et al 33 . Zhou et al showed that due to the large-scale soil and water conservation measures implemented in southwest China, the increase in vegetation cover in the Jialing River basin has significantly increased, while the effect of increased vegetation cover on rivers in the basin is mainly focused on sediment changes, while the effect of runoff changes is not obvious 22 .…”
Section: Discussionsupporting
confidence: 88%
“…and needs of farmers would increase success of end-users and other stakeholders to ensure effective co-production [6]. Regarding management decisions from analysis and monitoring of processed NDVI images, methods to systematize and improve efficiency in using NDVI image-based resources seeking to increase agricultural productivity have been recently tackled [3], [5], [7], [8]- [14]. NDVI images can correlate spectral and spatial digital information with the practical interest variables of usefulness in Precision Agriculture.…”
Section: Palabras Clavementioning
confidence: 99%